Impact of radiopacified bone cement on radiotherapy dose calculation. (April 2020) - Crowe, Scott B.; Bennett, Jane; Lathouras, Marika; Lancaster, Craig M.; Sylvander, Steven R.; Chua, Benjamin; Bettington, Catherine S.; Lin, Charles Y.; Kairn, Tanya
Abstract: Background and purpose: Radiopacifiers are introduced to bone cements to provide the appearance of bone in kilovoltage (kV) radiographic images. For higher energy megavoltage (MV) radiotherapy treatment beams, however, these radiopacifiers do not cause a bone-like perturbation of dose. This study therefore aimed to determine the impact of the barium-contrasted plastic-based cement materials on radiotherapy dose calculations. Materials and methods: The radiological properties of a physical sample of bone cement were characterised by computed tomography (CT) imaging and transmission measurements. Monte Carlo simulations of percentage depth-dose profiles were performed to determine the possible dose error for MV treatment beams. Dose differences were then investigated for clinical volumetric modulated radiotherapy treatment plans, with and without density overrides applied. Results: Differences of up to 7% were observed at the downstream interface of a 0.6 cm thick bone cement layer, compared to bone. Differences in planning target volume dose-volume metrics varied between −0.5% and 2.0%. Conclusion: Before planning radiotherapy treatments for patients who have undergone cranioplasty, every effort should be made to identify whether a radiopacified bone cement has been implanted. Density overrides should be applied to minimise dose calculation errors, whenever bone cement is used.